2009
DOI: 10.1130/b26588.1
|View full text |Cite
|
Sign up to set email alerts
|

Erosional truncation of uppermost Permian shallow-marine carbonates and implications for Permian-Triassic boundary events: Reply

Abstract: Wignall et al. (2009) present two arguments that the erosional surface that we described is unrelated to the end-Permian mass-extinction event. First, they prefer to attribute erosion of uppermost Permian strata to subaerial exposure rather than to submarine carbonate erosion and/or dissolution. Second, they suggest that the erosion surface is not demonstrably younger than a sequence boundary within preextinction strata observed at Meishan and elsewhere. We are thankful for the interest in our study and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A conspicuous irregular surface is beneath the microbialite in Xiajiacao (Figs 3, 5), as observed in other PTBMs elsewhere in South China (Ezaki et al, 2003;Liu et al, 2007;Payne et al, 2007Payne et al, , 2009Collin et al, 2009;Wignall et al, 2009;Kershaw et al, 2012;Lehrmann et al, 2015).…”
Section: Origin Of Irregular Contact Between Microbialite and Skeletal Packstonesupporting
confidence: 66%
“…A conspicuous irregular surface is beneath the microbialite in Xiajiacao (Figs 3, 5), as observed in other PTBMs elsewhere in South China (Ezaki et al, 2003;Liu et al, 2007;Payne et al, 2007Payne et al, , 2009Collin et al, 2009;Wignall et al, 2009;Kershaw et al, 2012;Lehrmann et al, 2015).…”
Section: Origin Of Irregular Contact Between Microbialite and Skeletal Packstonesupporting
confidence: 66%
“…However, the interpretation is controversial (Wignall et al, 2009;Payne et al, 2009), with the fundamental issue being whether the dissolution features observed occurred during subaerial exposure (i.e., during weathering) or while submerged, in response to ocean acidification. A broader search for dissolution features and diagnostic criteria is underway.…”
Section: Calcification Crisis During End-permian Extinctionmentioning
confidence: 99%
“…An erosional surface at the formational boundary has been observed in many other Tethyan sections (Turkey, South China, Japan), but the origin (subaerial-karstic vs. submarine-dissolution surfaces) and connection with the main extinction phase are greatly debated (e.g. Payne et al, 2007Payne et al, , 2009Wignall et al, 2009). The occurrence of oxidized bioclasts both in the uppermost Bulla and basal Tesero members of the Werfen Fm in some basinward sections (e.g.…”
Section: Rich Marine Assemblages Prelude the Extinction (In 1 Sequencmentioning
confidence: 98%